Attention to negative emotion is related to longitudinal social network change: The moderating effect of interdependent self‐construal. Issue 8 (27th October 2014) - Li, Tianyuan; Fung, Helene H; Isaacowitz, Derek M; Lang, Frieder R
<x xml:space="preserve">Abstract</x> Aim Many previous studies have investigated older adults' attentional preference toward different emotions. Interdependent self‐construal is identified to be an important moderator of this phenomenon. However, despite the important social functions of emotions, the social consequence of older adults' emotional preferences in attention have not yet been examined. The current study tested how older adults' attentional preferences assessed in the laboratory influenced changes in their real‐life social network, and how interdependent self‐construal moderated this effect. Methods A total of 45 older adults aged 60–84 years participated in an eye‐tracking session that measured their attentional preference to emotional faces versus neutral faces. After that, participants completed the Self‐Construal Scale. Participants' social network was then assessed by the Social Convoy Questionnaire twice over a 2‐year period. Results Interdependent self‐construal significantly moderated the effect of attention to angry and sad faces on older adults' real‐life social network changes. For older adults with a higher level of interdependent self‐construal, more attention toward negative emotions was related to longitudinal decreases in the number of their emotionally close social partners. Conclusions The present study shows the important role of attentional preferences in older adults' social network maintenance. It identified a real‐life macro level social outcome of a micro level laboratory phenomenon, which can be an important direction for future research. Geriatr Gerontol Int 2015; 15: 1079–1086.